Educação linguística : percepções dos professores de língua inglesa do ensino médio - (:unkn) unknown (Universidade Estadual de Goiás, 2025)
This research aims to understand the perception of high school English teachers regarding Digital Information and Communication Technologies (DICT), especially in the post-pandemic context. To achieve this, the study will analyze the experiences of teachers from the state public school system in Itaberaí - GO, exploring their pedagogical practices with digital technologies and identifying challenges and opportunities. This is a qualitative and netnographic study, adopting the content analysis technique for interpreting the collected data. Data collection was conducted using Google Forms, allowing teachers to share their experiences and impressions regarding the use of digital technologies in English language teaching. The main authors used to discuss linguistic education were Bagno (2005), Ferraz (2018), Pereira (2018), Duboc (2018), and Miquelante et al. (2022). Regarding digital literacy, key authors included Kleiman (2005), Soares (2006), Cope and Kalantzis (2010), Melo (2012), Rojo (2012), Meyers et al. (2013), Freitas (2019), Kalantzis and Cope (2020), Flores and Freitas (2020), and Ferraz (2018). To discuss digital literacy in linguistic education, the research was based on studies by Paiva (2019), Silva (2020), Ribeiro, Moreira, and Araújo (2022), and Joaquim (2023). The approach to linguistic education and digital technologies relied on the works of Day and Savedra (2015), Monte Mór (2017), Braga, Pinheiro, and Rocha (2019), and Kalantzis and Pinheiro (2020). Regarding the evolution of digital technologies in education, this study is supported by the works of Rodrigues (2015), Moran (2015), Monte Mór (2017), and Gordiano and Andriola (2022). Finally, studies addressing the use of digital technologies in English language teaching include Lévy (2010), Gee (2018), Meneses (2019), Avelar and Freitas (2019), Barbosa (2020), Lima (2021), and Oliveira (2021). The data reveal that, although many high school English teachers have considerable experience, they face significant challenges regarding the use of DICT. While most recognize the potential of these technologies to make lessons more dynamic and engaging, barriers related to continuous training and inadequate infrastructure still exist. The lack of specific training and structural resources limits the full integration of DICT in English language teaching.
Linguistic education : perceptions of high school english language teachers
Keywords: Tecnologias digitais; Ensino de inglês; Professores; Ensino médio; Inclusão digital; Digital technologies; English teaching; Teachers; High school; Digital inclusion; LINGUISTICA, LETRAS E ARTES::LETRAS; LETRAS::LINGUAS ESTRANGEIRAS MODERNAS